2005
DOI: 10.1136/jcp.2004.018895
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4A, CDC6, and MCM5: predictive biomarkers in cervical preinvasive neoplasia and cervical cancer

Abstract: Aim: To analyse and compare expression patterns of three potential biomarkers-p16 INK4A , CDC6, and MCM5-and evaluate their use as predictive biomarkers in squamous and glandular cervical preinvasive neoplasia. Methods: Immunocytochemical analysis of p16 INK4A, MCM5, and CDC6 expression was performed on 20 normal, 38 cervical intraepithelial neoplasia 1 (CIN1), 33 CIN2, 46 CIN3, 10 squamous cell carcinoma, 19 cervical glandular intraepithelial neoplasia (cGIN), and 10 adenocarcinoma samples. Staining intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
151
2
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(164 citation statements)
references
References 50 publications
5
151
2
6
Order By: Relevance
“…CDC6 appears to be preferentially unregulated in highgrade preinvasive neoplasia (CIN3) and in invasive cervical carcinoma and in adenocarcinoma. 19,20 In this study, simple linear regression analysis revealed a linear increase (estimated slope ¼ 12.1, R 2 ¼ 0.085, P-value o0.045) in the level of CDC6 mRNA expression in the normal cervix, CIN3 and invasive carcinoma. These results at the mRNA level correlate strongly with previous findings for CDC6 phenotypic protein expression using immunohistochemical analysis, which demonstrated a linear relationship between increasing CDC6 protein expression and increasing severity of cervical dysplasia.…”
Section: Cdc6 Quantitative Taqman Rt-pcrmentioning
confidence: 51%
See 4 more Smart Citations
“…CDC6 appears to be preferentially unregulated in highgrade preinvasive neoplasia (CIN3) and in invasive cervical carcinoma and in adenocarcinoma. 19,20 In this study, simple linear regression analysis revealed a linear increase (estimated slope ¼ 12.1, R 2 ¼ 0.085, P-value o0.045) in the level of CDC6 mRNA expression in the normal cervix, CIN3 and invasive carcinoma. These results at the mRNA level correlate strongly with previous findings for CDC6 phenotypic protein expression using immunohistochemical analysis, which demonstrated a linear relationship between increasing CDC6 protein expression and increasing severity of cervical dysplasia.…”
Section: Cdc6 Quantitative Taqman Rt-pcrmentioning
confidence: 51%
“…Indeed, MCM5 mRNA expression closely correlates with findings at the phenotypic protein expression level, which demonstrated an increase in MCM5 protein expression with increasing severity of dysplasia, using immunohistochemical techniques. 19 These findings suggest that increased MCM5 protein expression in cervical dysplasia is a consequence of transcriptional upregulation. One possible suggestion for upregulation of MCM5 mRNA in cervical dysplasia put forward by Ishimi et al 14 could be that high-risk human papillomavirus oncoprotein E7 binding to the retinoblastoma protein releases inhibition on E2F allowing transcriptional upregu- CDC6 and MCM5 mRNA expression in CIN N Murphy et al lation of MCM5.…”
Section: Cdc6 Quantitative Taqman Rt-pcrmentioning
confidence: 93%
See 3 more Smart Citations